TGF-β-Containing Small Extracellular Vesicles From PM2.5-Activated Macrophages Induces Cardiotoxicity - Hu, Xiaoqi; Chen, Mo; Cao, Xue; Yuan, Xinyi; Zhang, Fang; Ding, Wenjun (Frontiers in Cardiovascular Medicine, 2022)
Numerous epidemiological and experimental studies have demonstrated that the exposure to fine particulate matter (aerodynamic diameter <2.5 μm, PM2.5) was closely associated with cardiovascular morbidity and mortality. Our previous studies revealed that PM2.5 exposure induced cardiac dysfunction and fibrosis. However, the corresponding underlying mechanism remains largely unaddressed. Here, PM2.5-induced cardiotoxicity is presented to directly promote collagen deposition in cardiomyocytes through the transforming growth factor-β (TGF-β)-containing small extracellular vesicles (sEV). The sEV transition may play an important role in PM2.5-induced cardiac fibrosis. Firstly, long-term PM2.5 exposure can directly induce cardiac fibrosis and increase the level of serum sEV. Secondly, PM2.5 can directly activate macrophages and increase the release of tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and TGF-β-containing sEV. Thirdly, TGF-β-containing sEV increases the expression of α-smooth muscle actin (α-SMA), collagen I, and collagen III in mouse cardiac muscle HL-1 cells. Finally, TGF-β-containing sEV released from PM2.5-treated macrophages can increase collagen through the activation of the TGF-β-Smad2/3 signaling pathway in HL-1 cells from which some fibroblasts involved in cardiac fibrosis are thought to originate. These findings suggest that TGF-β-containing sEV from PM2.5-activated macrophages play a critical role in the process of increasing cardiac collagen content via activating the TGF-β-Smad2/3 signaling pathway.